Trade Policy and Economic Growth in Sub-Saharan Africa: A Panel Data Approach - Asfaw, Henok Arega (American Journal of Trade and Policy, 2014)
Despite a number of multi-country case studies utilizing comparable analytical frameworks, numerous econometric studies using large cross-country data sets, and important theoretical advances in growth theory, there is still disagreement among economists concerning how a country’s international economic policies and its rate of economic growth interact. The central objective of this paper is to empirically assess the link between trade policy and economic growth in Sub-Saharan Africa countries. Apart from reviewing different literatures, this study also provides empirical evidence on the relationship between economic growth and trade policies. In doing so, the study used a panel data covering 47 Sub-Saharan Africa countries over the periods 2000 – 2008. The estimation support claims that openness to international trade stimulates both economic growth and investment. Besides, trade policies such as average weighted tariff rate and real effective exchange rate have both direct and indirect impacts on economic growth.